Changing distribution of rotavirus A genotypes circulating in Japanese children with acute gastroenteritis in outpatient clinic, 2014–2020. Issue 7 (July 2022) - Okitsu, Shoko; Khamrin, Pattara; Hikita, Toshiyuki; Thongprachum, Aksara; Pham, Ngan Thi Kim; Hoque, Sheikh Ariful; Hayakawa, Satoshi; Maneekarn, Niwat; Ushijima, Hiroshi
Abstract: Background: Rotavirus A (RVA) is a major cause of severe acute gastroenteritis (AGE) in infants and children worldwide. In Japan, two kinds of rotavirus vaccines have been introduced as voluntary vaccines in 2011 and 2012, respectively, and launched into the national vaccine program in October 2020. Methods: In this study, we investigated prevalence of RVA and their molecular characterization in the stool samples collected from infants and children with AGE who visited one outpatient clinic in Japan, from July 2014 to June 2020, during voluntary vaccination with two kinds of rotavirus vaccines. Results: The RVA detection rates decreased from 44.7 % in 2014–2015 to 35.4 % in 2018–2019, whereas in 2019–2020 the numbers of samples collected were dramatically decreased and none of RVA was detected. During this study period, rotavirus vaccination rates in this area increased from 32.4 % to 62.2 %. Distribution of RVA VP7 (G), VP4 (P), and VP6 (I) genotypes in this area had changed year by year; the major genotype combinations were G1P[8]I1 and G1P[8]I2 in 2014–2015, G2P[4]I2 and G9P[8]I1 in 2015- 2016, G1P[8]I1 and G8P[8]I2 in 2017–2018, and G8P[8]I2 in 2018–2019. Phylogenetic analysis demonstrated that VP7 nucleotide sequences of G1 were genetically diverse compared with those of other G genotypes in this study. Meanwhile, predominance of unusual G2P[8]I1, G2P[8]I2 and mixed P genotypes were observed only in 2016–2017, but did not carry on in 2017–2019. The equine-like G3 was detected only in 2016–2017. Conclusions: The results revealed diversity of RVA genotypes and the genotype combinations have changed year by year in Japan, during the study period of 2016–2020.